Implementasi Manajemen Kelas dan Relevansinya Dengan Hasil Belajar Siswa di Madrasah Ibtidaiyah Quraniah 8 Palembang - Ibrahim Ibrahim; Nita Nur Cahyani; Mardiah Astuti; Febriyanti Febriyanti (Sekolah Tinggi Agama Islam Sumatera Medan, 2021)
This study aims to analyze the implementation of classroom management and its relevance to improving learning outcomes, with the focus of the study on two things: (1) classroom management implementation, (2) supporting and inhibiting factors for classroom management implementation. This research was conducted at Madrasah Ibtidaiyah Quraniah 8 Palembang, using qualitative research methods based on descriptive studies. In this study, the informants were the principal, homeroom teacher and administrative staff. The data were obtained by using observation, interview and documentation techniques. The data analysis technique is through data reduction, data presentation, and drawing conclusions, the validity of the data in this study uses the validity of the data by triangulation. The results of this study indicate that the implementation of classroom management at MI Quraniah 8 Palembang has been going well but not optimally. This implementation is manifested in the arrangement of facilities consisting of the arrangement of the study room, the arrangement of the seats, the arrangement of the air ventilation, the arrangement of the light. In addition, setting learning tools and setting the learning atmosphere. The inhibiting factors include the lack of awareness of students in fulfilling their rights and responsibilities in carrying out their duties. Then inadequate facilities, buildings and classroom facilities. Meanwhile, the supporting factors are teachers who are active and creative in directing the development of their students. Classroom management is related to improving student learning outcomes, the more comfortable students learn, the better student learning outcomes.